Review of the genus Onconeura Andersen et Sæther (Diptera: Chironomidae), with the description of four new species from Brazil - Wiedenbrug, Sofia; Mendes, Humberto F.; Pepinelli, Mateus; Trivinho-Strixino, Susana (Zootaxa, 2009)
Four new species of Onconeura Andersen et Sæther are described from Brazil, O. japi, O. oncovolsella and O. similispina as male, female, pupa and larva, and O. cascatinha as male and pupa. Additionally four pupal morphotypes are included. One new described species has associated COI DNA barcoding gene. The material studied was collected in the States of Mato Grosso, Minas Gerais, Rio de Janeiro, São Paulo and Rio Grande do Sul. Keys to the known species are given for all life stages.